The norms of answerability : social theory between Bakhtin and Habermas - Nielsen, Greg Marc, 1953- (Albany : State University of New York Press, 2002)
Annotation Greg M. Nielsen brings Mikhail Bakhtin's ethics and aesthetics into a dialogue with social theory that responds to the sense of ambivalence and uncertainty at the core of modern societies. Nielsen situates a social theory between Bakhtin's norms of answerability and Jurgen Habermas's sociology, ethics, and discourse theory of democracy in a way that emphasizes the creative dimension in social action without reducing explanation to the emotional and volitional impulse of the individual or collective actor. Some of the classical sources that support this mediated position are traced to Alexander Vvedenskij's and Georg Simmel's critiques of Kant's ethics, Hermann Cohen's philosophy of fellowship, and Max Weber's and George Herbert Mead's theories of action. In the shift from Bakhtin's theory of interpersonal relations to a dialogic theory of societal events that defends the bold claim that law and politics should not be completely separated from the specificity of ethical and cultural communities, a study of citizenship and national identity is developed. Book jacket.
Machine generated contents note: Introduction: Theory on the Borders of Sociology -- Ch. 1 Diversity and Transcultural Ethics -- Disciplinary Orientations -- Decentered Subjects and Critiques of Discourse Ethics -- Creative Side of the Normative -- Normative Side of Creativity -- Between the Creativity and Normativity of the Act -- Ch. 2 Communicative Action or Dialogue? -- Communicative Action and Moral Development -- Limits of Universal Reason -- Dialogism: Mixing the Word and Style -- Ch. 3 World of Other's Words -- Bakhtin and Voloshinov on the Subject of the Utterance -- Social and Ethical Worlds of Dialogue in Dostoevsky -- Frankfurt Tradition -- Habermas's Break -- Genres of Discourse in Literature and in Theory -- From Dostoevsky to Calvino -- Convergence and Difference -- Ch. 4 On the Sources of Young Bakhtin's Ethics (Kant, Vvedenskij, Simmel, Cohen) -- Kant's Three Postulates -- ^ Vvedenskij's Fourth Postulate -- Simmel's Shadow -- Bakhtin and the Formal Ought -- Cohen's "Discovery of Man as Fellowman" -- Influences and Steps -- Ch. 5 Action and Eros (Kant-Weber-Bakhtin) -- Kant: Duties Toward the Body Concerning the Sexual Impulse -- Weber: Action, Ethics, and Eros -- Bakhtin: The Fourth Postulate and Body-Dialogue -- Eros and Action Today -- Ch. 6 Reflexive Subjectivity (Mead-Bakhtin) -- Philosophical and Disciplinary Orientations -- Between Consciousness and Language: The Ambiguity of Experience -- Murder, Confession, and Community -- Why the Subject Is Behind Us -- Action Inside and Outside the Subject -- Ch. 7 Citizenship and National Identity -- On the Dialogue Between Ethnos and Demos -- Identity -- For and against the Nation -- Ch. 8 Dialogue on the Nation in Postnational Times -- Nation as a Sociology of Culture: The Quebec Case -- ^
Includes bibliographical references (pages 225-239) and index.
Print version record.
English.
JSTOR
Keywords: Social norms; Sociology -- History; Normes sociales; Sociologie -- Histoire; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Social norms; Sociology; Sociale normen; Sociologie; Ethiek; Theorieën.; History